2019
DOI: 10.1089/biores.2018.0040
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Human Papillomavirus Self-Sampling Among a National Sample of Women in the United States

Abstract: As human papillomavirus (HPV) self-sampling continues to emerge as a potential cervical cancer screening strategy in the United States, it is necessary to examine women's acceptability of this screening approach. Furthermore, since several HPV self-sampling devices exist, it is important to determine if women's preferences differ by device type. We conducted an online survey in Fall 2017 with a national sample of women ( n = 605) ages 21–65 years (the recommended age range for cervical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“… 55 , 56 , 113 In a recent study in the US, women were more willing to use devices that closely resemble a basic swab than three other swab- and brush-based devices. 51 Interestingly, this study also found women’s willingness to use a specific brush device varied by sexual orientation: sexual minority women were more willing to use the HerSwab device than heterosexual women.…”
Section: Types Of Devices For Hpv Self-samplingmentioning
confidence: 61%
See 2 more Smart Citations
“… 55 , 56 , 113 In a recent study in the US, women were more willing to use devices that closely resemble a basic swab than three other swab- and brush-based devices. 51 Interestingly, this study also found women’s willingness to use a specific brush device varied by sexual orientation: sexual minority women were more willing to use the HerSwab device than heterosexual women.…”
Section: Types Of Devices For Hpv Self-samplingmentioning
confidence: 61%
“… 82 , 135 On the other hand, nearly 20% of women indicate that they do not have any concerns about using a self-sample. 51 To address women’s concerns, positive feedback from large-scale studies should be presented through public-awareness campaigns, including data showing that most women are able to successfully obtain an adequate sample. 51 , 96 , 102 , 115 …”
Section: Lessons In Women’s Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“… 61 The USPSTF also endorses primary HPV testing–only strategies. 62 The pandemic may thus provide an opportunity to expand use of patient-collected HPV self-swabs which have been reported to be acceptable to patients and noninferior to physician collection, 63 , 64 , 65 potentially leading to increased screening of underrepresented populations such as transgender or gender nonconforming patients. 66 , 68 , 67 For immunocompromised patients requiring more urgent follow-up but who are at high risk if they acquire COVID-19, providers can consider integrating self-collection kits that are able to be returned by mail into current practice.…”
Section: Cancer Screeningmentioning
confidence: 99%
“…Consequently, a cheap, practical, and highly sensitive solution with high specificity is always welcomed by the health authorities. In this context, the self-collection of vaginal cells delegates the responsibility to the women themselves to minimize the negative impact that any religious and cultural constraints may cause, and indecisive women can be encouraged to participate in screening programs [5][6][7]. The methodological premise of self-sampling is simple, since the material is sent to a reference laboratory that will evaluate the presence of HPV.…”
Section: Introductionmentioning
confidence: 99%